Christian justice and public policy - Forrester, Duncan B. (Cambridge studies in ideology and religion, 1997)
Disagreements about justice are not simply academic matters. They create problems for practice and for policy-making. In a morally fragmented society in which 'nobody knows what justice is' issues such as wages policy, punishment and poverty become particularly difficult to handle. People striving to act justly are often uncertain how this might be done. Secular theories such as those of Rowls, Hayek, Habermas and modern feminist theorists, examined here, give some guidance for problems of justice that arise on the ground, but have serious limitations. This book argues that Christian theology, although it can no longer claim to provide a comprehensive theory of justice, can provide insights into justice - 'theological fragments' - which give illumination, challenge some aspects of the conventional wisdom, and contribute to the building of just communities in which people may flourish in mutuality and hope.